The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1038/sj.jim.2900317
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of TNT and related aminotoluenes in groundwater aquifer slurries under different electron-accepting conditions

Abstract: The transport and fate of pollutants is often governed by both their tendency to sorb as well as their susceptibility to biodegradation. We have evaluated these parameters for 2,4,6-trinitrotoluene (TNT) and several biodegradation products. Slurries of aquifer sediment and groundwater depleted TNT at rates of 27, 7.7 and 5.9 microM day-1 under methanogenic, sulfate-reducing and nitrate-reducing conditions, respectively. Abiotic losses of TNT were determined in autoclaved controls. Abiotic TNT loss and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 1 publication
2
28
0
Order By: Relevance
“…Williams et al (41) observed significant TNT disappearance from contaminated soil in both thermophilic and mesophilic composting conditions. A similar study on TNT remediation has also been reported for groundwater aquifer slurries by Kromholt et al (23). If physiological conditions optimal for enzymatic reactions favoring TNT reduction can be maintained, the remediation would be more effective.…”
Section: Discussionsupporting
confidence: 64%
“…Williams et al (41) observed significant TNT disappearance from contaminated soil in both thermophilic and mesophilic composting conditions. A similar study on TNT remediation has also been reported for groundwater aquifer slurries by Kromholt et al (23). If physiological conditions optimal for enzymatic reactions favoring TNT reduction can be maintained, the remediation would be more effective.…”
Section: Discussionsupporting
confidence: 64%
“…Nitrate respiraton conditions gave the best degradation rate with a consortium of soil bacteria (33), whereas methanogenesis seemed to be optimal with slurries of aquifer sediment (135).…”
Section: Vol 65 2001 Metabolism Of Nitroaromatic Compounds 341mentioning
confidence: 99%
“…Numerous studies examining the reduction of TNT by intact bacterial cells report either transformation to ADNTs without the accumulation of any intermediates (6,7,24,27,35,42,46,49) or the transient accumulation of HADNTs with subsequent transformation to ADNTs (13, 15, 28, 38, 58, 59). However, experiments using single enzymes to transform TNT and other nitroarenes produce hydroxylaminoarenes exclusively, without any production of aminoarenes (22,43,45,50,54).…”
Section: Discussionmentioning
confidence: 99%
“…(39), Vellonella spp. (40), nitrate-reducing bacteria (6,35), Pseudomonas spp. (42), Enterobacter cloacae (23), and Salmonella enterica serovar Typhimurium (60).…”
mentioning
confidence: 99%